Immigrant Examination Behavior - Gil S. Epstein; Shahar Sansani (Institute of Labor Economics (IZA), 2019)
In this paper, we estimate differences in examination behavior between immigrants and natives, by examining differences in the propensity to forego a passing grade on a final exam in order to retake that final exam. Retaking a final exam involves some level of uncertainty, so differences in examination behavior may be due to differences in motivation, risk-taking, and discipline. We find that immigrants are about 2 percentage points more likely to retake a passed exam than natives. This represents a large difference given a baseline retake rate of about 6.5 percentage points.
Keywords: J15; I23; D81; 330; immigrant-native differences; examination behavior; uncertainty; motivation